KARAKTERISASI PERTUMBUHAN DAN HASIL PADI SAWAH VARIETAS IR 64, CIHERANG DAN INPARI 32 DENGAN PEMBERIAN MUTAGEN ETIL METAN SULFONAT - Fauziah, Afifah; Novalina, Novalina (Universitas Jambi, 2026)
The use of superior varieties is one of the important factors in efforts to increase productivity and production of lowland rice. However, each superior variety has advantages and disadvantages. The use of the chemical mutagen Ethyl Methane Sulfonate (EMS) is expected to increase genetic diversity and improve the characteristics of superior rice varieties. This research aims to determine the effect of EMS on the growth and production of several lowland rice varieties. The research was carried out at the Screen House, Faculty of Agriculture, University of North Sumatra, October 2023 – March 2024. This research used a factorial Randomized Block Design (RBD), with two treatment factors namely variety (IR64, Ciherang, Inpari 32) and EMS concentration (0%, 0.5%, 1%) and three replications. EMS treatment was carried out when the seeds were soaked for 4 hours. The rice seeds are sown in trays. Selected seedlings are planted in plastic tubs. The observation variables consisted of seedling growth, plant growth, flowering age, harvest age, yield and component of yield. Data were analyzed using ANOVA and Duncan's test at α 5%. The research results showed that rice variety factor had a significant effect on seedling growth, plant growth, number of panicles and panicle length. The highest number of tillers and number of panicles are found in the Ciherang variety. The EMS concentration factor had a significant effect on seedling height and panicle length. Interaction factors have a significant effect on seedling height.